ҚИЁСИЙ ТАДҚИҚОТЛАРНИНГ АСОСИЙ ЙЎНАЛИШЛАРИ - Шаниязов, Б.Ж.; Алламбергенова, Г.К.; Алламбергенова, Б.К. (SCIENCE and SOCIETY, 2022)
The relevance of this article is determined by the importance of the study of comparative aspects in modern linguistics, the implementation of comparative research. Although the linguistic units available in all languages and their types often look similar, it is important to determine whether each language has internal capabilities, similarities and differences. The article concludes that the study of such features from the point of view of comparative linguistics will undoubtedly find a solution to the problems that have arisen in areas such as language teaching, translation studies.